1971
DOI: 10.3109/00016347109157334
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual Syndrome and Physical Exercise

Abstract: The relationship between premenstrual syndrome and physical exercise was studied with the aid of questionnaires in a series of 748 female university students. Girls who practised sports showed less symptoms of central nervous tension, particularly headache. Menstrual dys‐mennrrhoea also was less frequent in the athletes than in the control group. On the other hand no correlation was observed between premenstrual dysmenorrhoea, oedema and the practice of sports. Gymnastics had practically no effect on the vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
1
2

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 10 publications
0
2
1
2
Order By: Relevance
“…Identifying modifiable risk factors, such as physical activity, is important to help improve premenstrual symptom severity in women who may not need or want a pharmacological remedy. However, unlike some prior studies [8,1115,17,18], we did not find a lower prevalence of PMS or premenstrual symptoms in women who participated in high levels of physical activity compared to women who participated in lower levels or no physical activity. We also did not find that a relationship between physical activity and PMS was confounded by BMI.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Identifying modifiable risk factors, such as physical activity, is important to help improve premenstrual symptom severity in women who may not need or want a pharmacological remedy. However, unlike some prior studies [8,1115,17,18], we did not find a lower prevalence of PMS or premenstrual symptoms in women who participated in high levels of physical activity compared to women who participated in lower levels or no physical activity. We also did not find that a relationship between physical activity and PMS was confounded by BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…To the contrary, a study that included 748 college-aged women found that the percentage of women experiencing premenstrual and menstrual low back pain, premenstrual and menstrual pelvic pain, premenstrual and menstrual headache, premenstrual nervousness, irritability, anxiety, depression and fatigue were all significantly higher (p<0.05) in women studying in other programs compared to those studying at the Institute of Physical Education. These findings, however, were based on the assumption that physical education students were more active, though this assumption was not validated [15]. …”
Section: Discussionmentioning
confidence: 99%
“…[ 14 29 ] Positive results for relieving somatic and psychologic symptoms of PMS were reported in a sham-controlled trial of reflexology. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…A fellelhető irodalmak legnagyobb részében a sport hatását vizsgálták a premenstruációs tünetek súlyosságára, illetve azok előfordulását sportolók körében (Timonen & Procopé, 1971;Czajkowska & mtsai., 2015;Takeda & mtsai., 2016).…”
Section: Bevezetésunclassified